COMPARATIVE RESULTS OF STUDYING THE COURSE OF PREGNANCY AND CHILDBIRTH WITH CONSERVATIVE AND SURGICAL CORRECTION OF CERVICAL INCOMPETENCE - Vagabova, Sh.B.; Aliyeva, E.M.; Asadova, Sh.S.; Bayramova, E.V. (World of Medicine and Biology, 2025)
The purpose of this study was to research the methods of correction of cervical incompetence, a comparison of the features of the course of pregnancy and childbirth with conservative and surgical correction of cervical incompetence. Correction of cervical incompetence was performed in 100 pregnant women: in 50 with a conservative pessary and in 50 with two U-shaped cervical sutures. Treatment was carried out in hospital settings in 95 % of cases, and on an outpatient basis in 5 % of cases. In contrast to surgical correction of cervical incompetence, conservative correction by installing an obstetric unloading pessary allows for a non-traumatically resolved pregnancy, with a positive result. With conservative correction, the risk of miscarriage, the number of premature births and late miscarriages decreased by half. The results show that conservative correction allowed for pregnancy to be carried to term and a viable fetus to be born in 93.3 % of cases.